2019
DOI: 10.1101/571679
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deciphering the ‘m6A code’ via quantitative profiling of m6A at single-nucleotide resolution

Abstract: N6-methyladenosine (m 6 A) is the most abundant modification on mRNA, and is implicated in critical roles in development, physiology and disease. The ability to map m 6 A using immunoprecipitation-based approaches has played a critical role in dissecting m 6 A functions and mechanisms of action. Yet, these approaches are of limited specificity, unknown sensitivity, and unable to quantify m6A stoichiometry. These limitations have severely hampered our ability to unravel the factors determining where m6A will be… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…In mammalian cells, m 6 A levels are mostly static even during key developmental stages such as stem cell differentiation 39,44 , with deregulation of METTL3 and increases in global m 6 A of only 25% being sufficient to inhibit differentiation, promote cell growth, and maintain tumorigenicity 25 . Although the m 6 A-demethylases Alkbh5 and FTO may modulate methylation levels in some cases 17 , m 6 A is generally deposited early and maintained throughout the life of an mRNA transcript 45 .…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian cells, m 6 A levels are mostly static even during key developmental stages such as stem cell differentiation 39,44 , with deregulation of METTL3 and increases in global m 6 A of only 25% being sufficient to inhibit differentiation, promote cell growth, and maintain tumorigenicity 25 . Although the m 6 A-demethylases Alkbh5 and FTO may modulate methylation levels in some cases 17 , m 6 A is generally deposited early and maintained throughout the life of an mRNA transcript 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, single-nucleotide m 6 A sequencing approaches have revealed the presence of such sequences and have indicated that the m 6 A-modified transcriptome is more diverse than previously appreciated. 48,51 Finally, we envision that site-specifically modified random RNA libraries can be applied to probe the effect of diverse epitranscriptomic marks and sequence context on fundamental nucleic acid-related processes including protein−RNA binding, catalysis by modification writer and eraser enzymes, and templated polymerization. Combined with nucleic acid index-…”
Section: ■ Discussionmentioning
confidence: 99%
“…Nevertheless, the finding that YTHDF1/2 can bind tightly to noncanonical m 6 A-containing motifs suggests that related m 6 A sequences may exist in the transcriptome. Indeed, single-nucleotide m 6 A sequencing approaches have revealed the presence of such sequences and have indicated that the m 6 A-modified transcriptome is more diverse than previously appreciated. , …”
Section: Discussionmentioning
confidence: 99%